Cytotoxicity of Gymnopilus purpureosquamulosus extracts on hematologic malignant cells through activation of the SAPK/JNK signaling pathway. - Rich Milton Dulay (Public Library of Science (PLoS), 2021)
Treatment of hematologic malignancies is a formidable challenge for hematologists and there is an urgent need to identify safe and efficacious agents either via synthesis in the laboratory or isolation from natural products. Here, we report the cytotoxicity of extracts from mushroom Gymnopilus purpureosquamulosus Høil (G. pps) and describe its molecular mechanisms. Using leukemia, lymphoma and multiple myeloma cell lines, 28-35 ppm G. pps extract inhibited cell proliferation by ~46-79%, which correlates with activation of apoptosis as indicated by increase in annexin V-positive cells (~5-8-fold), production of reactive oxygen species (~2-3-fold), cells in sub G0/G1 phase (~3-13-fold), caspase 3 enzymatic activity (~1.6-2.9-fold), DNA fragmentation, PARP1 cleavage and down-regulation of prosurvival proteins. Mitochondrial membrane potential decreased and leakage of pro-apoptotic factors to cytoplasm was observed, consistent with the activation of intrinsic apoptosis. Western blot analysis showed activation of the ASK1-MEK-SAPK/JNK and ASK1-P38 MAPK pathways possibly due to changes in the cellular redox status as suggested by decreased protein levels of peroxiredoxin, thioredoxin and thioredoxin reductase. Moreover, antioxidant N-acetylcysteine alleviated the cytotoxicity of G. pps. Pharmacological inhibition of SAPK/JNK and P38 alleviated the G. pps-mediated cytotoxicity. The extract activated apoptosis in leukemia and lymphoma patient cell samples but not in mononuclear cells from healthy donors further supporting the therapeutic values of G. pps for hematologic malignancies.